The most dangerous game [videorecording (DVD)] - Schoedsack, Ernest B., 1893-1979; McCrea, Joel, 1905-1990; Wray, Fay, 1907-2004; Banks, Leslie, 1890-1952; Connell, Richard Edward, 1893-1949 (Criterion collection, 1999)
A madman on his island fortress, tired of pursuing game, becomes obsessed with the idea of hunting the most dangerous game of all-- man.